Sistem Informasi Online di SD Al Wasliyah 2 demi Meningkatkan Aksebilitas dan Informasi Sekolah - Elsera, Marina; Ramdhani, Rizky Budi; Afriansyah, Rizky; Kurniawan, Bayu Tri (Al-DYAS, 2024)
Al wasliyah 2 private elementary school has been using printed leaflets to advertise various events and information about the school such as information on the admission of new students and information on other activities. However, with the increasing use of technology and the need for more effective communication, websites have become one of the identities of an institution or school in cyberspace. The purpose of this activity is to build a website-based online information system using the bootstrap framework. This application is designed using PHP and MySQL because it is web-based, this application has the ability to be accessed anywhere so that admins can edit and post content or information related to school information needs. The expected result is to replace print media so that various forms of information and activities are expected to be more neatly and efficiently arranged.